Phenolic acids and quercetin from Korean black raspberry seed protected against acetaminophen-induced oxidative stress in mice. (December 2015) - Choi, Mi-Hee; Shim, Soon-Mi; Kim, Gun-Hee
Highlights: Black raspberry seeds are produced during juice and winemaking procedure. Phenolic acids and flavonoids in seed extracts were determined. Pretreatment of seed extracts protected the liver damage induced by acetaminophen. Seed extracts inhibited oxidative damage to lipid, protein, and DNA in liver. Fresh and wine seed extracts as byproducts have a potential for hepatoprotection. Abstract: The Korean black raspberry seed extracts are hypothesised to protect against acetaminophen-induced hepatotoxicity. Male mice were divided into five groups: (1) normal treated, (2) APAP-treated, (3) fresh seed extract (FSE) treated, (4) wine-processed seed extract (WSE) treated, and (5) silymarin-treated. The amounts of gallic acid (8.23 mg/g extract) and ellagic acid (11.22 mg/g extract) in WSE were significantly higher than those in FSE. Both protocatechuic acid (3.81 mg/g extract) and quercetin (7.41 mg/g extract) were only found in WSE. In both FSE and WSE groups, the activity of AST and ALT significantly decreased, while the antioxidant markers including CAT, SOD, GPx, and GSH were restored in a dose-dependent manner. The inhibition of the oxidative damage to lipid, protein, and DNA by Korean black raspberry seed extract was more effective in WSE than FSE. These results suggest that phenolic acids and quercetin from wine-processed seed could have therapeutic potential in hepatotoxicity.